Comment On The Paper ?Neutralization Of Bioleach Liquors? By B.M. Nyombolo, J.W. Neale, And P.J. Van Staden - In The Journal Of SAIMM, Vol. 100. No. 7. Pp. 403?408 - J. M. Schaekers (The Southern African Institute of Mining and Metallurgy, 2001)
In the first part of the article, the authors give a broad overview of the chemistry and some engineering aspects of bioleach processes, eventually leading to the important and critical issue of the stability of arsenic-containing residues, especially those derived from bioleaching of sulphidic gold ores. In the section ?Factors affecting arsenic stability? they give an excellent summary of the factors normally affecting the stability of such residues. This is followed by some valid comments on the suitability of a single leach test to evaluate the long-term stability of solid waste streams. However, they fail to mention that, up till now, no tests procedure has been accepted by either environmentalists or the mining/processing industry as a valid method to test the long-term stability of solid wastes. Their own method is no exception, although, like many others, it is useful to identify potential problems with solid wastes considered for disposal.